Effect of sport-specific constraints on aerobic capacity in high school field hockey players - Roberts, A. H.; Walden, A. J.; Carter, K. A.; Symons, T. B. (The Journal of Strength and Conditioning Research, 2022)
Many sports require the use of a mouth guard (MG) and carrying an object during play. Research has shown that individually these conditions can cause performance decrements; however, no research has been conducted into the effect of combining both mouth guard and stick with adolescent female field hockey players. This study aimed to determine the effects of MG and stick (STK) use on estimated aerobic capacity over the course of a season long training and competition period. Thirty-eight female high school field hockey players were separated into 2 groups: experimental (EXP—all training with MG-STK) or control (CTL—all training without MG-STK). Aerobic capacity was estimated using a multi-stage fitness test. Field hockey specific training prescribed by coaching staff was performed throughout the study, with testing at pre-, mid- and post-season. Subjects performed 2 sets of testing at each time point, first without MG-STK (WOMG-STK) and then with MG-STK. No main effect was observed in aerobic capacity estimations between groups; however, MG-STK testing reduced estimated aerobic capacity at each time point, regardless of the group (WOMG-STK: 37.4 ± 6. mL/kg/min vs. MG-STK: 33.2 ± 4. mL/kg/min; p < 0.01). Chronic use of MG-STK does not seem to negatively impact estimates of aerobic capacity over the course of a season in high school field hockey players. Therefore, players should be encouraged to use MGs during all training sessions as it increases safety and familiarity with no decrement in long-term physiological performance.